Effect of surface treatment and glazing in the two-body wear resistance of a hybrid ceramic after polymeric staining application - Grangeiro, Manasses Tercio Vieira [UNESP] (2021)
The present study evaluated the wear resistance of the characterization layer applied over a hybrid ceramic with different surface treatments against a zirconia antagonist. Eighty hybrid ceramic discs were prepared, polished and distributed in eight groups, according to the surface treatment before characterization and presence of a glaze layer (P, polished specimens - used as a reference; PG, polished specimens with glaze; E, acid etching; EG, acid etching + glaze; A, sandblasting; AG, sandblasting + glaze; S, self-etching silane; SG, self-etching silane + glaze). The specimens were subjected to physiological wear simulation with zirconia applicators (n = 10). The parameters for the wear simulation were: 15 N, horizontal movement of 6 mm, 1.7 Hz and 5000 cycles in distilled water. With the aid of a contact profilometer, R-z roughness parameter was analyzed in different periods of evaluation (after 0, 10, 100, 500, 1000 and 5000 cycles). R-z mean values were statistically analyzed using 3-way ANOVA (surface treatment x glaze presence x number of cycles), followed by Tukey test (alpha = 5%). ANOVA showed statistically significant differences among the groups considering the wear depth. And, significant interaction between the factors. However, as isolated factors, only surface treatment and number of cycles affected the staining wear rate (p < 0.05). Acid etching followed by glaze application was the most durable surface treatment to maintain the external staining on the hybrid ceramic surface when subjected to the two-body wear test.